A Brief Review of the Russia-Ukraine War’s Effect on the Global Economy - Li, Hong (Advances in Social Sciences Research Journal, 2022)
The war that Russia launched on Ukraine has aroused wide concern. It is believed that the war brought many effects since it caused a series of chain reactions. The war made the engaging countries stop supplying energy and agricultural products to other countries anymore. This article discusses whether these effects would change the world economy in terms of energy, in which Russia plays a dominant role in, and agriculture, in which Ukraine is of great importance. In the article, it is explained which nations are engaged and what their present situation is. Indeed, Russian energy is important. However, it is not the sole supplier. EU can find other alternative ways by using renewable energy, and so on. Meanwhile, Ukraine provided the majority of crops to the world. The war stopped the supply of that to other countries as the ports, which were used to transport them are controlled by Russia. Fortunately, there is a new agreement has been made between Russia and the EU so that some of the ports in Ukraine recovered transportation, releasing the pressure on the food crisis for low-income countries. In the long term, the effect of the war on the global economy remain to be seen. Moreover, Russia has been subject to varied degrees of sanctions, most notably the prohibition on the use of SWIFT by several Russian banks. It appears to have a more negative impact on nations that depend on Russia for their mineral and energy needs.